2014
DOI: 10.4149/bll_2014_117
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary thrombocytosis induced by exercise and environmental luminosity

Abstract: Abstract:Objectives: We investigated the exercise and different environmental luminosities effects on blood platelets count in order to identify primary and secondary thrombocytosis, respectively. Background: Platelets alteration has been associated with important pathological events, such as neurodegenerative diseases, and the count of these cells in bloodstream is infl uenced by several effects, including physical and chemical. Owing the diffi culty to study the aetiology of thrombocytosis in human models, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Additionally, several investigations involving animal models of different backgrounds were published. Some examples include methodological analyses (de Araujo et al, 2007; Beck et al, 2012; Sena et al, 2015), effects of periodized or non-periodized training (de Oliveira et al, 2007; de Araujo et al, 2012, 2013a, 2016; Scariot et al, 2016) effects of luminosity and time of day (Beck and Gobatto, 2013, 2016; Beck et al, 2014; Beck et al, 2014a,b) and comparion with the MLSS protocol (Rodrigues et al, 2016). …”
Section: Animal Models and The Lmtmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several investigations involving animal models of different backgrounds were published. Some examples include methodological analyses (de Araujo et al, 2007; Beck et al, 2012; Sena et al, 2015), effects of periodized or non-periodized training (de Oliveira et al, 2007; de Araujo et al, 2012, 2013a, 2016; Scariot et al, 2016) effects of luminosity and time of day (Beck and Gobatto, 2013, 2016; Beck et al, 2014; Beck et al, 2014a,b) and comparion with the MLSS protocol (Rodrigues et al, 2016). …”
Section: Animal Models and The Lmtmentioning
confidence: 99%
“…Over the years, the LMT has gained popularity around the world, and its application has been seen in several contexts including studies with diabetes (de Oliveira et al, 2007; Oliveira et al, 2010), thrombocytosis (Beck et al, 2014b) and wheelchair-racing athletes (Perret et al, 2012). Despite the fact that important concerns were arisen so far, some questions remain requiring discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Other experiments compared exercise during both circadian periods and systematically found that rats performed better at night [5,7]. In addition to the effect of the time of day, it is important to note that the environmental light employed for the exercise testing during the dark period (higher spontaneous physical activity, wakefulness period of nocturnal rats) can also influence the performance [8].…”
Section: Spontaneous Physical Activitymentioning
confidence: 99%
“…All of the subsequent procedures were performed at the time of day corresponding to the specific group. Special environmental illumination was employed for animals assessed during the dark period ( > 600 nm; < 15 lux), as described elsewhere [8]. From 76 to 89 days of age, all the rats were subjected to a water environment and swimming adaptation to avoid stress due to novelty during the exercise tests.…”
Section: Experimental Designmentioning
confidence: 99%
“…4,5). Rheological alterations are currently linked to morbidities such as: diabetes, hereditary disorders, sickle cell, myocardial infarction, paroxysmal nocturnal hemoglobinuria, sepsis, end stage renal disease, hypertension, strokes, endothelial function, vascular health, hemostasis in athletes and blood transfusions and cancer (Hung et al 1991;Pechan et al 1991;McHedlishvili and Maeda 2001;Ahmad and El-Sayed 2003;Meiselman 2003, 2010;Piagnerelli et al 2003;Babu and Singh 2004;Meiselman et al 2007;Forsyth et al 2012;Serroukh et al 2012;Beck et al 2014;Giovanna 2014;Hierso et al 2014;Buttari et al 2015;Heber and Volf 2015;Ertan et al 2017). Interestingly, we also observed many rheological alterations in our "healthy" pilot study participants (Figs.…”
Section: Introductionmentioning
confidence: 99%